CO2 migration and distribution in multiscale-heterogeneous deep saline aquifers - Yuan Wang (Yandy Scientific Press, 2021)
Large volumes of carbon dioxide (CO2 ) captured from carbon emission source can be stored in deep saline aquifers as a mean of mitigating climate change. The deep saline aquifers are naturally heterogeneous at multiple scales. It is important to generate representative multiscale heterogeneous ﬁelds of various hydrogeologic properties and understand storage safety by studying CO2 migration and distribution in such ﬁelds. In this work, a new multiscale heterogeneous model with partly ﬁne multi-facies heterogeneous domain is proposed. A method based on transition probability theory is referred to establish a multi-facies model. A new multiscale heterogeneous model with partly ﬁne multi-facies heterogeneous domain is built up according to the categorized permeability data obtained from the Geological Carbon Storage Frio site in USA. TOUGH2/ECO2N is applied to simulate CO2 migration and distribution in such a multiscale heterogeneous model. The CO2 plume shows obvious viscous ﬁngering and non-uniform migration both in layered and vertical directions, implying vertical and horizontal heterogeneity which cannot be represented by a single-scale model or simulated with the assumption of homogeneous formation. The proﬁle of CO2 migration shown in the numerical simulation at a time of 10 days is in a good accordance with the seismic data of Frio situ in qualitative and quantitative aspects.